Gehaltesorg en koste-effektiewe dienslewering deur middel van 'n geoutomatiseerde pasientklassifikasiestelsel. - Mirinda Coetsee (AOSIS, 1985)
A patient classification system is used to classify patients according to the acuity of their condition and the amount of care which they need in order to determine staffing needs. Such a system enables optimal provision of nursing staff thus ensuring cost-effective quality care. A patient classification system must be tailored to the needs of each hospital to ensure reliability. There is an adaptable computer software program which is able to do all the calculations for a patient classification system. It provides valuable daily, weekly and monthly print-outs - such as summaries of patient acuity and staffing requirements for each unit and for the hospital as a whole.